Ultramafic complexes and associated mineral deposits in the Precambrian of eastern Minas Gerais, Brazil - Angeli, N. [UNESP]; Choudhuri, A. (Springer, 1985)
Based on field work, prospection and petrographic studies ultramafic complexes and their mineral deposits from eastern Minas Gerais in southeastern Brazil are generally outlined to form a basis for future investigations in this region. The bodies dealt with occur at Ipanema, Córrego Novo, Bela Vista de Minas, Rio Pomba and Liberdade. These ultramafic bodies are generally enclosed in high-grade gneisses and consist of serpentinized peridotites and harzburgites which were metamorphosed together with their country rocks in upper amphibolite to granulite facies. Weathering of these rocks gives rise to nickeliferous laterite, while metamorphism has resulted in anthophyllite asbestos and talc deposits. © 1985 Springer-Verlag.
Keywords: GEOPHYSICS - Rock Properties; MAGNESIUM COMPOUNDS - Evaluation; PETROLOGY - Petrography; BRAZIL; MAFIC-ULTRAMAFIC COMPLEXES; MINERAL DEPOSITS; PETROGRAPHIC CHARACTER; MINERALOGY